Hearing loss in Menière's disease and sensorineural low-frequency fluctuating hearing loss without vertigo: are there any differences?. (2nd October 2018) - Albera, Andrea; Canale, Andrea; Dagna, Federico; Gervasio, Carmine Fernando; Albera, Roberto
Abstract: Aims: In previous decades Menière's disease (MD) has been classified into four different categories: certain, definite, probable and possible. Recently, in the need to overcome critical issues in the diagnosis, the Bárány Society proposed new diagnostic criteria on MD excluding the certain and possible categories. Nevertheless, this updated classification raises the risk that many possible MD, namely isolated sensorineural low-frequency fluctuating hearing loss (SLFHL), would not be considered as precursors of definite MD. The aim of the present study is, therefore, to compare clinical aspects and evaluate differences between hearing loss in definite MD and in isolated SLFHL, which could be useful for clinical diagnostic and prognostic purposes. Materials and methods: A total of 662 patients suffering from definite MD ( n = 447) and isolated SLFHL ( n = 215) according to the 1995 American Academy of Otorhinolaryngology Head and Neck Surgery guidelines were retrospectively considered along a 5-year period. Pure-tone audiometry was performed on all patients. Results: A significantly higher incidence of bilateral pathology and longer duration of disease resulted in patients with definite MD. Differently, no significant differences were demonstrated between the groups either in terms of age at diagnosis or gender. The average 500–3000 Hz hearing threshold was significantly higher in definite MD in comparison with SLFHL. Conclusions: Results support the assumption of the difficulty to perform a differential diagnosis between definite MD and SLFHL and suggest the extent of hearing loss as the main diagnostic element in predicting the onset of vertigo, therefore an evolution to definite MD.